Cultural differences in on-line sensitivity to emotional voices: comparing East and West - Liu, Pan; Rigoulot, Simon; Pell, Marc D. (Frontiers in Human Neuroscience, 2015)
Evidence that culture modulates on-line neural responses to the emotional meanings encoded by vocal and facial expressions was demonstrated recently in a study comparing English North Americans and Chinese (Liu et al., 2015). Here, we compared how individuals from these two cultures passively respond to emotional cues from faces and voices using an Oddball task. Participants viewed in-group emotional faces, with or without simultaneous vocal expressions, while performing a face-irrelevant visual task as the EEG was recorded. A significantly larger visual MMN was observed for Chinese versus English participants when faces were accompanied by voices, suggesting that Chinese were influenced to a larger extent by task-irrelevant vocal cues. These data highlight further differences in how adults from East Asian versus Western cultures process socio-emotional cues, arguing that distinct cultural practices in communication (e.g., display rules) shape neurocognitive activity associated with the early perception and integration of multi-sensory emotional cues.